Chemical Disequilibria, Lithospheric Thickness, and the Source of Ocean Island Basalts. (2nd March 2019) - Grose, Christopher J; Afonso, Juan C
Abstract: We examine REE (Rare-Earth Element) and isotopic (Sr–Hf–Nd–Pb) signatures in OIB (Ocean Island Basalts) as a function of lithospheric thickness and show that the data can be divided into thin- (<12 Ma) and thick-plate (>12 Ma) sub-sets. Comparison to geophysically constrained thermal plate models indicates that the demarcation age (∼12 Ma) corresponds to a lithospheric thickness of about 50 km. Thick-plate OIB show incompatible element and isotopic enrichments, whereas thin-plate lavas show MORB-like or slightly enriched values. We argue that enriched signatures in thick-plate OIB originate from low-degree melting at depths below the dry solidus, while depleted signatures in MORB and thin-plate OIB are indicative of higher-degree melting. We tested quantitative explanations of REE systematics using melting models for homogeneous fertile peridotite. Using experimental partition coefficients for major upper mantle minerals, our equilibrium melting models are not able to explain the data. However, using a new grain-scale disequilibrium melting model for the same homogeneous lithology the data can be explained. Disequilibrium models are able to explain the data by reducing the amount of incompatible element partitioning into low degree melts. To explore new levels of detail in disequilibrium phenomena, we employ the Monte-Carlo Potts model to characterize the textural evolution of a microstructure undergoing coarsening and phase transformation processes simultaneous with the diffusive partitioning of trace elements among solid phases and melt in decompressing mantle. We further employ inverse methods to study the thermochemical properties required for models to explain the OIB data. Both data and theory show that OIB erupted on spreading ridges contain signatures close to MORB values, although E-MORB provides the best fit. This indicates that MORB and OIB are produced by compositionally indistinguishable sources, although the isotopic data indicate that the source is heterogeneous. Also, a posteriori distributions are found for the temperature of the thermomechanical lithosphere-asthenosphere boundary ( TLAB ), the temperature in the source of OIB ( Tp, oib ) and the extent of equilibrium during melting (i.e. grain size). TLAB has been constrained to 1200–1300°C and Tp, oib is constrained to be <1400°C. However, we consider the constraints on Tp, oib as a description of all OIB to be provisional, because it is a statistical inference from the global dataset. Exceptional islands or island groups may exist, such as the classical 'hotspots' (Hawaii, Reunion, etc) and these islands may originate from hot sources. On the other hand, by the same statistical arguments their origins may be anomalously hydrated or enriched instead. Mean grain size in the source of OIB is about 1–5 mm, although this is also provisional due to a strong dependence on knowledge of partition coefficients, ascent rate and the melting function. We also perform an inversion in which partition coefficients were allowed to vary from their experimental values. In these inversions TLAB and Tp, oib are unchanged, but realizations close to equilibrium can be found when partition coefficients differ substantially from their experimental values. We also investigated bulk compositions in the source of OIB constrained by our inverse models. Corrections for crystallization effects provided ambiguous confirmations of previously proposed mantle compositions, with depleted mantle providing the poorest fits. We did not include isotopes in our models, but we briefly evaluate the lithospheric thickness effect on isotopes. Although REE data do not require a lithologically heterogeneous source, isotopes indicate that a minor enriched component disproportionately contributes to thick-plate OIB, but is diluted by high-degree melting in the generation of thin-plate OIB and MORB.